Efektivitas Bahan Ajar IPA Berbasis Inkuiri Terbimbing (BAIPABIT) untuk Meningkatkan Kemampuan Berargumen Peserta Didik - Deni Apriana Senjaharmini; A Wahab Jufri; Jamaluddin Jamaluddin (Jurnal Pijar Mipa, 2019)
Abstrak: This study aims to determine the effectiveness of guided inquiry-based science teaching materials (BAIPABIT) on the ability to argue junior high school students. This research was conducted in class VII of Suralaga 1 Public Middle School in the odd semester 2018/2019 academic year. The sample of 43 students was divided into two research classes, the control class and the experimental class. The type of research used is an experimental study with pre testpost test group design. Data analysis on the effectiveness of BAIPABIT on students 'ability to argue by using normalized gain indexes and students' classical completeness. The results showed that the N-Gain score in the control class was 30.77% and the experimental class was 57.57% and the classical completeness analysis showed that the classical completeness of the control class was 33.33% and the experimental class was 72.73%. This proves that guided inquiry based science material (BAIPABIT) is more effective in improving the ability to argue junior high school students than teaching materials commonly used by teachers.ÃÂ Kata Kunci :ÃÂ  Science Teaching Materials, Guided Inquiry, Argument ability